Study of Differences and Effects of Parental Communication and Student Learning Motivation in Elementary Schools - Amin, Alfauzan; Alimni, Alimni; Kurniawan, Dwi Agus; Azzahra, Miftahul Zannah; Septi, Sabila Eka (International Journal of Elementary Education, 2021)
The problem behind this research is the lack of parental communication on students' learning motivation at the elementary school level. This study aims to see how important parental communication is to students' learning motivation in the learning process of Islamic religious education. This type of research is a mixed method, namely quantitative and qualitative with an explanatory design. The subjects in this study were parents and elementary school students. Data collection techniques used in this study were the distribution of questionnaires and interviews. The data analysis method used is quantitative descriptive analysis by testing the findings using spps; record results; and draw conclusions. Quantitative description by distributing questionnaires and conducting interviews. The results showed that there were differences and influences between parental communication and student learning motivation in Islamic religious education subjects.